Effect of heat treatment on the physical and mechanical properties of compression and opposite wood of Black pine - Türker Dündar; Ümit Büyüksarı; Erkan Avcı; Hüseyin Akkılıç (BioResources, 2012)
The effect of commercial heat treatment on physical and mechanical properties of compression wood (CW) and opposite wood (OW) of black pine (Pinus nigra Arnold) was investigated. Black pine logs containing CW were cut parallel to the pith and separated into CW and OW sections. A commercial heat treatment process was applied to pine lumber at 180 and 210 ºC for 3 hours. Water absorption (WA), contact angle (CA), swelling, modulus of rupture (MOR), modulus of elasticity (MOE), and impact bending strength (IBS) were measured. The results showed that heat treatment decreased water absorption and swelling of the CW and OW of black pine. Heat treatment at 210 °C temperature decreased the longitudinal swelling of CW by 51.4%. Higher immersion time lowered the effect of heat treatment on the WA values. The CA values of the CW and OW increased due to heat treatment. Heat treatment reduced the MOR, MOE, and IBS values. The results indicated that MOR, MOE, and CA values were highly affected in the CW; on the other hand, the IBS value was highly affected in the OW by heat treatment compared to control groups. The results indicate that heat-stabilized CW can be used more widely and effectively in the forest products industry.